An Analytical Short-Circuit Current Calculation Method for Full-Power Wind Turbines under Complete Fault Ride-Through Processes - YUAN Shuai, XIAO Jiaan, TAO Jun, CUI Haohan, CHAO Pupu, LI Weixing, A Minfu, WANG Liqiang, ZHONG Ming (Dianli jianshe)
Accurate calculation of short-circuit current throughout the fault ride-through process of wind turbines is a critical prerequisite for the analysis and control of modern power systems. Current studies on the short-circuit current of full-converter wind turbines primarily focus on the initial fault stage， with limited attention given to the entire fault ride-through process. This paper presents a comprehensive analysis of the dynamic behavior of short-circuit current across the entire fault ride-through process， based on the manufacturer-packaged model of a practical full-converter wind turbine. A complete model of the turbine’s control strategy is constructed to derive analytical expressions for the transient behavior across four key stages： fault occurrence transient， steady-state during fault duration， post-fault transient， and post-fault recovery. An analytical method for calculating short-circuit current throughout the fault ride-through process is proposed. The validity of the proposed method is demonstrated by comparing the analytical calculation results with short-circuit current test results obtained from the manufacturer’s black-box packaged model.